On Internally Statically and Kinematically Determinate Problems in the Linear Theory of Shells - Rychter, Z. (Engineering Transactions, 1985)
Modified conditions of static and kinematic determinateness for the interior domain of an arbitrary elastic shell are found on the basis of estimates of the error of shell theory solutions in an energetic norm. The conditions are illustrated by an example and confronted with their earlier counterparts formulated in terms of the residual error in shell theory equations.